THE USE OF SONGS FOR LEARNING INTEGRATED LITERACY - dewi puspitasari; Chusna Maulida; Norman Novianto (Universitas Muria Kudus, 2020)
Inspired from the STEM educational reform, the teaching of two subjects (mathematics and language) integratedly has inspired the researchers to conduct an activity to engage the young learners. Song is taken into consideration as it offers exciting learning experience, and that song lyrics is beneficial to carry information, elicit memory and activate thought and ideas. Rooted from the Vigotsky’s ZPD, an intervention to the learning was initiated to arouse students’ enthusiasm. The result indicated that though some students were still shy, majority students showed eagerness to learn.